2019
DOI: 10.1155/2019/6372786
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TGR5 Partially Alleviates High Glucose-Induced Cardiomyocyte Injury by Inhibition of Inflammatory Responses and Oxidative Stress

Abstract: High glucose- (HG-) induced cardiomyocyte injury is the leading cause of diabetic cardiomyopathy, which is associated with the induction of inflammatory responses and oxidative stress. TGR5 plays an important role in the regulation of glucose metabolism. However, whether TGR5 has cardioprotective effects against HG-induced cardiomyocyte injury is unknown. Neonatal mouse cardiomyocytes were isolated and incubated in a HG medium. Protein and mRNA expression was detected by western blotting and RT-PCR, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Numerous evidences have indicated that oxidant stress plays an essential role in DM-associated cardiovascular complication progression and is often correlated with CMEC dysfunction [30]. Previous studies have been showed that hyperglycemia could induce oxidant stress injury in mammal cells, such as mouse microvascular endothelial cells [31], cardiomyocyte [32], and HK-2 cells [33]. Consistent with findings of these other studies, our results showed that hyperglycemia enhanced intracellular ROS and MDA production, and inhibited SOD activity in CMECs.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous evidences have indicated that oxidant stress plays an essential role in DM-associated cardiovascular complication progression and is often correlated with CMEC dysfunction [30]. Previous studies have been showed that hyperglycemia could induce oxidant stress injury in mammal cells, such as mouse microvascular endothelial cells [31], cardiomyocyte [32], and HK-2 cells [33]. Consistent with findings of these other studies, our results showed that hyperglycemia enhanced intracellular ROS and MDA production, and inhibited SOD activity in CMECs.…”
Section: Discussionsupporting
confidence: 91%
“…Under oxidative stress, Keap1 is inactivated, Nrf2 releases from Keap1 and translocates into the nucleus, where it triggers the expression of endogenous antioxidant/detoxifying proteins such as HO-1 and NQO-1. [38,39] Our www.advancedsciencenews.com www.mnf-journal.com results indicated that the expression levels of Nrf2 and its downstream factors HO-1 and NQO-1 were decreased and the level of Keap1 was increased in diabetic mice. Accordingly, the SYR treatment effectively up-regulated the expression of Nrf2, HO-1, and NQO-1 and down-regulated the expression of Keap1 in diabetic mice.…”
Section: Discussionmentioning
confidence: 92%
“…Diabetic cardiomyopathy is a health‐threatening disease with myocardial damage (Dillmann, 2019). Hyperglycemia‐caused apoptosis, increased reactive oxygen species (ROS), and inflammation responses in cardiomyocytes (CMs) are the main mechanisms of diabetic cardiomyopathy (L. Deng et al, 2019; J. Y. Deng et al, 2019; Zhao, Liu, & Li, 2019; M. X. Zhao et al, 2017). The existing study has shown that the cellular and molecular mechanisms of heart injury caused by high glucose (HG) are complex and multifactorial (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%